Relationship between weekends catch-up sleep and risk of aging - Nan Yao; Liuyi Shen; Linrui Qi; Wenqiang Li; Chenan Liu; Fuzhou Han; Ning Duan; Guoyong Yu; Jun Qu (PLoS ONE, 2025)
Background Sleep has been proven to be associated with various chronic diseases and aging. However, many individuals fail to achieve recommended sleep durations on weekdays and opt for compensatory sleep during weekends. This study aims to investigate the relationship between weekend catch-up sleep (CUS) and aging. Methods All participants were sourced from NHANES 2017–2018. Using the sleep questionnaire, we obtained participants’ sleep timings and durations on weekdays and weekends. Weekend CUS was identified as an extension in average weekend sleep duration. Biological age is a biomarker for evaluating biological aging, and its difference from actual age is used to determine aging. Weighted logistic regression analysis was employed to explore the relationship between CUS and aging. Results A total of 4,713 participants were included in this study, with an average age of 47.54 ± 16.94 years. 50.6% of individuals experienced CUS. Compared to individuals without CUS, participants with CUS had a 20% lower risk of aging (OR = 0.80, 95% CI: 0.63−1). Specifically, participants who engaged in CUS for 0−1 hour showed a 23% lower risk of aging (OR = 0.77, 95% CI: 0.61–0.96), and those with CUS for 1−2 hours had a 20% lower risk of aging (OR = 0.80, 95% CI: 0.65–0.98). Stratifying by bedtime, the relationship between CUS and reduced aging risk is only observed in individuals who usually go to sleep before midnight and have CUS less than 2 hours. Conclusion The 0–2 hour CUS is associated with a reduced risk of aging, and this relationship is more significant in participants who go to bed early and have healthy sleep patterns.